Of woman born?The literary topic of the genos gynaikonand its impact on Plato and Aristotle - Sonna, Valeria (Revista Archai, 2023)
To say that we are all of woman born seems a truism. This is, as Rich puts it, the one unifying,undeniable experience shared by women and men: those months we spend inside a woman’s body, developing. However, it is common to find in the civic discourse of Greek cities the idea that women have no relation to the origin of the species. Women are oftenrepresented as a separate and self-contained group, the genos gynaikon, which is added to the preexisting anthropos genos. The hypothesis of the present paper argues that there are two conceptual aspects to the genos gynaikonnarrative: (i) the ambiguity in the classification of women and (ii) the secondary place assigned to them with respect to the origin of humanity. My main goal is to show that the topic of the genos gynaikonis present, through these conceptual aspects, in the Platonic and Aristotelianconception of reproduction and sexual difference.